A bibliometric analysis of the Fasting-Mimicking Diet - Lin, Xiaoxiao; Gao, Yue (Frontiers in Nutrition, 2024)
The Fasting-Mimicking Diet (FMD) is a nutritional strategy that involves significantly reducing calorie intake for a specific period to mimic the physiological effects of fasting while still providing the body with nutrition. Our study aimed to conduct a bibliometric study to explore the latest publishing trends and areas of intense activity within the sphere of FMD. We extracted data on FMD publications from the Web of Science Core Collection (WOSCC) database. The bibliometric analysis was conducted by WOSCC Online Analysis Platform and VOSviewer 1.6.16. In total, there were 169 publications by 945 authors from 342 organizations and 25 countries/regions, and published in 111 journals.The most productive country, organization, author, and journal were the USA, the University of Southern California, Valter D Longo, and Nutrients, respectively. The first high-cited document was published in Ageing Research Reviews and authored by Mattson et al in 2017. In this study, they discuss the various health benefits of FMD including improved metabolic health, weight management, and even potential effects on delaying aging processes and reducing the risk of chronic diseases. In conclusion, our study is the first bibliometric analysis of the FMD. The main research hotspots and frontiers were FMD for cancer, FMD for metabolic-related diseases, and FMD for cognitive improvement. FMD may have some potential benefits for multiple diseases which should be further investigated.